Pre-clinical toxicity of a combination of berberine and 5-aminosalicylic acid in mice. (November 2016) - Li, Yan-hong; Zhang, Man; Fu, Hai-bo; Xiao, Hai-tao; Bian, Zhao-xiang
Abstract: Our previous study demonstrated that a combination of alternative medicine berberine and conventional 5-aminosalicylic acid (5-ASA) showed promise to be a novel therapeutic strategy for ulcerative colitis (UC). This present study aims to sketch the pre-clinical toxicity profile of this combination (1:10 dose ratio) on mice. In acute toxicity test, the determined median lethal dose (LD50 ) was 278.7 mg/kg berberine plus 2787 mg/kg 5-ASA. The results from subacute toxicity test demonstrated that no toxic signs of clinical symptoms, no significant changes in hematological or biochemical parameters were detected in mice treated with 14 + 140, 28 + 280 or 56 + 560 mg/kg of berberine plus 5-ASA treatment. Histological examinations revealed that accompanied with an increase in spleen weight, frequently recorded enlargement and white pulp hyperplasia of spleen were detected in mice when exposed to three doses of combination treatments. Further in vitro assessment suggested that the spleen toxicity was originated from berberine by its inhibition in cell viability and cell proliferation of lymphocytes. The results of this study indicate that the combination of berberine and 5-ASA shows a slight toxic effect on spleen, suggesting that this combination should be used with caution for patients. Highlights: The determined LD50 of combination was 278.7 mg/kg berberine plus 2787 mg/kg 5-ASA in mice. Mild spleen toxicity was observed in mice from the subacute toxicity assessment. Enlargement, weight increase and white pulp hyperplasia were observed on spleen of mice, indicating spleen toxicity associated with this berberine/5-ASA combination. The detected spleen toxicity of this combination was originated from berberine by its inhibiting effects in cell viability and cell proliferation of lymphocyte.